Determinación de ganancia de peso y estatura en ovinos de diferentes edades en el ceypsa - Jijón Jerez, Darío Mauricio (2016)
This research work was carried out in the Cotopaxi province, Eloy Alfaro Parish, Salache neighborhood, in the Technical University of Cotopaxi at “Agricultural science and Natural resources Academic Unit”. In this research 39 ovine of different races such as dorper, merino, katadin, frisiona where used because the project of the institution already had them. The relevant research collected data and genetic improvement of ovine. Then, the measurement of weight gain and height of ovine was made through the use of weight balance and measuring tape for height, this activity was made each seven days during a determined time. Once, collected the weekly weight of each one of the animals we proceeded to calculate through formulas to get the results and realize if the weight gain exists and finally the determination of the ovine age. After analyzing the weight results of each one animal it was detected that not all animals gain weight or height just a few animals could do it.